y= -3(2x+5)(4x-3)

For further actions, you may consider blocking this person and/or reporting abuse

We're a place where learners ask for help for their tasks and share their knowledge.

y= -3(2x+5)(4x-3)

For further actions, you may consider blocking this person and/or reporting abuse

XCJ C_2012 -

StunnaShades45 -

Alan Herrera -

:) -

travis s -

Winner -

LiveLaughLoveLearn -

Love.Live.Laugh -

thecreativeone121 -

Brittz -

coolmom -

Ryan -

Yesenia Barber -

marshay64 -

Graham P -

itsmariaokay -

Phyllis Cook -

:) -

:) -

Banana Manna -

## Answers (1)

y=-3(2x+5)(4x-3)

To find the x-intercept, substitute in 0 for y and solve for x.

(0)=-3(2x+5)(4x-3)

Since x is on the right-hand side of the equation, switch the sides so it is on the left-hand side of the equation.

-3(2x+5)(4x-3)=(0)

If any individual factor on the left-hand side of the equation is equal to 0, the entire expression will be equal to 0.

(2x+5)=0_(4x-3)=0

Set the first factor equal to 0 and solve.

(2x+5)=0

Remove the parentheses around the expression 2x+5.

2x+5=0

Since 5 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 5 from both sides.

2x=-5

Divide each term in the equation by 2.

(2x)/(2)=-(5)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=-(5)/(2)

Set the next factor equal to 0 and solve.

(4x-3)=0

Remove the parentheses around the expression 4x-3.

4x-3=0

Since -3 does not contain the variable to solve for, move it to the right-hand side of the equation by adding 3 to both sides.

4x=3

Divide each term in the equation by 4.

(4x)/(4)=(3)/(4)

Simplify the left-hand side of the equation by canceling the common factors.

x=(3)/(4)

The final solution is all the values that make -3(2x+5)(4x-3)=(0) true.

x=-(5)/(2),(3)/(4)